2021
DOI: 10.1016/j.cub.2020.09.090
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Activation of Dorsal Raphe Serotonergic Neurons Increases Pupil Size

Abstract: Summary Transient variations in pupil size (PS) under constant luminance are coupled to rapid changes in arousal state, 1 , 2 , 3 which have been interpreted as vigilance, 4 salience, 5 or a surprise signal. 6 , 7 , 8 Neural control of such fluctuations presumably involves multiple brain regions 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 58 publications
11
102
2
Order By: Relevance
“…More specifically, we found that the change in pupil size was correlated with change in performance such that the more 5-HTP constricted the pupil during a session, the more it also impaired performance. In contrast to our results, SSRIs have been shown to dilate the pupil (McDougal and Gamlin, 2011), as does phasic activation of serotonergic neurons (Cazettes et al, 2020). Furthermore, serotonin syndrome, associated with pathologically high levels of serotonin, is also associated with pupil dilation (Alusik et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…More specifically, we found that the change in pupil size was correlated with change in performance such that the more 5-HTP constricted the pupil during a session, the more it also impaired performance. In contrast to our results, SSRIs have been shown to dilate the pupil (McDougal and Gamlin, 2011), as does phasic activation of serotonergic neurons (Cazettes et al, 2020). Furthermore, serotonin syndrome, associated with pathologically high levels of serotonin, is also associated with pupil dilation (Alusik et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, Ulrich et al (2016) argued that, via serotoninergic output, the dorsal raphe nucleus downregulates the medial prefrontal cortex (a key structure of the DMN) during flow. Phasic serotonin responses in this nucleus have also been found to influence pupil responses (Cazettes et al, 2021). Therefore, future research may want to try to disentangle the specific influences of the various neuromodulatory systems.…”
Section: Concluding Remarks and Future Researchmentioning
confidence: 99%
“…This so-called “task-evoked” pupil response is modulated in amplitude by task demands, behavioral performance, and surprise [13, 14, 15, 16, 17, 18, 19, 20, 21]. Pupil responses covary with sweating and cardiac activity [22, 23], measures of peripheral autonomic activity, as well as spiking activity in the locus coeruleus [24, 25, 26, 27], basal forebrain [24, 28, 25], and dorsal raphé [20], sources of cortical norepinephrine, acetylcholine, and serotonin, respectively. Based on these observations, many studies have used pupil size as a non-invasive measure of arousal level [29, 30, 31, 32, 33].…”
Section: Introductionmentioning
confidence: 99%